Heart rate response during a simulated Olympic boxing match is predominantly above ventilatory threshold 2: a cross sectional study - de Lira CA; Peixinho-Pena LF; Vancini RL; Fachina RJ; de Almeida AA; Andrade MS; da Silva AC (Dove Medical Press, 2013)
Claudio Andre Barbosa de Lira,1 Luiz Fernando Peixinho-Pena,2 Rodrigo Luiz Vancini1,2 Rafael Júlio de Freitas Guina Fachina,3,4 Alexandre Aparecido de Almeida,2 Marília dos Santos Andrade,2 Antonio Carlos da Silva2 1Setor de Fisiologia Humana e do Exercício, Universidade Federal de Goiás (UFG), Câmpus Jataí, Jataí, GO, Brazil; 2Departamento de Fisiologia, Universidade Federal de São Paulo (UNIFESP), São Paulo, SP, Brazil; 3Departamento de Ciência do Esporte, Faculdade de Educação Física (FEF), Universidade Estadual de Campinas (UNICAMP), Campinas, Brazil; 4Confederação Brasileira de Basketball (CBB), Rio de Janeiro, Brazil Abstract: The present study aimed to describe heart rate (HR) responses during a simulated Olympic boxing match and examine physiological parameters of boxing athletes. Ten highly trained Olympic boxing athletes (six men and four women) performed a maximal graded exercise test on a motorized treadmill to determine maximal oxygen uptake (52.2 mL · kg-1 · min-1 ± 7.2 mL · kg-1 · min-1) and ventilatory thresholds 1 and 2. Ventilatory thresholds 1 and 2 were used to classify the intensity of exercise based on respective HR during a boxing match. In addition, oxygen uptake (VO2) was estimated during the match based on the HR response and the HR-VO2 relationship obtained from a maximal graded exercise test for each participant. On a separate day, participants performed a boxing match lasting three rounds, 2 minutes each, with a 1-minute recovery period between each round, during which HR was measured. In this context, HR and VO2 were above ventilatory threshold 2 during 219.8 seconds ± 67.4 seconds. There was an increase in HR and VO2 as a function of round (round 3 < round 2 < round 1, P < 0.0001).These findings may direct individual training programs for boxing practitioners and other athletes. Keywords: heart rate, physiological profile, intermittent exercise, combat sports, boxing